Patient-reported outcomes for diabetes and hypertension care in low- and middle-income countries: A scoping review. - Sarah Masyuko; Carrie J Ngongo; Carole Smith; Rachel Nugent (PLoS ONE)
Introduction Patient-reported outcome measures (PROMs) assess patients' perspectives on their health status, providing opportunities to improve the quality of care. While PROMs are increasingly used in high-income settings, limited data are available on PROMs use for diabetes and hypertension in low-and middle-income countries (LMICs). This scoping review aimed to determine how PROMs are employed for diabetes and hypertension care in LMICs. Methods We searched PubMed, EMBASE, and ClinicalTrials.gov for English-language studies published between August 2009 and August 2019 that measured at least one PROM related to diabetes or hypertension in LMICs. Full texts of included studies were examined to assess study characteristics, target population, outcome focus, PROMs used, and methods for data collection and reporting. Results Sixty-eight studies met the inclusion criteria and reported on PROMs for people diagnosed with hypertension and/or diabetes and receiving care in health facilities. Thirty-nine (57%) reported on upper-middle-income countries, 19 (28%) reported on lower-middle-income countries, 4 (6%) reported on low-income countries, and 6 (9%) were multi-country. Most focused on diabetes (60/68, 88%), while 4 studies focused on hypertension and 4 focused on diabetes/hypertension comorbidity. Outcomes of interest varied; most common were glycemic or blood pressure control (38), health literacy and treatment adherence (27), and acute complications (22). Collectively the studies deployed 55 unique tools to measure patient outcomes. Most common were the Morisky Medication Adherence Scale (7) and EuroQoL-5D-3L (7). Conclusion PROMs are deployed in LMICs around the world, with greatest reported use in LMICs with an upper-middle-income classification. Diabetes PROMs were more widely deployed in LMICs than hypertension PROMs, suggesting an opportunity to adapt PROMs for hypertension. Future research focusing on standardization and simplification could improve future comparability and adaptability across LMIC contexts. Incorporation into national health information systems would best establish PROMs as a means to reveal the effectiveness of person-centered diabetes and hypertension care.